Systems of Cryogenic Gas Supply to Preserved Organs - Shubin, N. A. (Problems of Cryobiology and Cryomedicine, 2008)
The effect of different current cryopreservation methods of biological material on human and animal organs were investigated. It has been shown that all of them more or less result in significant morphological changes in investigated objects and loss of their viability as a functional unit. For this problem solving the basically new method of low temperature cooling has been suggested.